2015
DOI: 10.1016/j.quaint.2014.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Levantine intermediate water hydrodynamic and bottom water ventilation in the northern Tyrrhenian Sea over the past 56,000 years: New insights from benthic foraminifera and ostracods

Abstract: Foraminifera and ostracods have been quantitatively studied in core MD01-2472, from the upper continental\ud slope (at water depth of 501 m), to evaluate their relationship with bottom water condition\ud variability and decipher the control of the Levantine IntermediateWater (LIW) current on benthic faunas.\ud The occurrence of reworked ostracod species (originating from the continental shelf) and, the presence of\ud shallow water Elphidium/Ammonia benthic foraminifera are used to estimate the degree of along-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 148 publications
4
18
0
Order By: Relevance
“…For this time period, a generally good vertical mixing due to wind activity is supported by the presence of deep‐dwelling planktic species such as Globorotalia truncatulinoides (Mojtahid et al, ). Similar benthic community changes as those we found in our record were interpreted as responding to a period of a better ventilation within a general context of sluggish circulation over the AHP (Abu‐Zied et al, ; Kuhnt et al, ; Minto'o et al, ), a feature confirmed by modeling (Grimm et al, ). An enhanced ventilation of bottom waters would explain the increase of the benthic δ 13 C, which together with the high values of planktic δ 13 C (i.e., high productivity) would explain the close to zero Δδ 13 Cp‐b.…”
Section: Discussionsupporting
confidence: 87%
“…For this time period, a generally good vertical mixing due to wind activity is supported by the presence of deep‐dwelling planktic species such as Globorotalia truncatulinoides (Mojtahid et al, ). Similar benthic community changes as those we found in our record were interpreted as responding to a period of a better ventilation within a general context of sluggish circulation over the AHP (Abu‐Zied et al, ; Kuhnt et al, ; Minto'o et al, ), a feature confirmed by modeling (Grimm et al, ). An enhanced ventilation of bottom waters would explain the increase of the benthic δ 13 C, which together with the high values of planktic δ 13 C (i.e., high productivity) would explain the close to zero Δδ 13 Cp‐b.…”
Section: Discussionsupporting
confidence: 87%
“…Similar processes have likely occurred in the past. During cold periods bottom water masses were better ventilated (Cacho et al, 2000;Minto'o et al, 2015) and faster (Toucanne et al, 2012) in the Mediterranean Sea. More arid and cold climatic conditions during cold intervals could favour the production of denser LIW (Cacho et al, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Increases of ostracod abundance and species richness as well as an assemblage change comparable to the Melilla CWC mound have been reported in the Younger Dryas of the Mediterranean from non-CWC related settings. Angue Minto'o et al (2015) report a shift from a Paracypris polita dominated assemblage during the last glacial period to a diverse assemblage in the Younger Dryas with higher percentages of Krithe spp. and Macrocyprididae comparable to the development in OA2.…”
Section: Wider Palaeoenvironmental Contextmentioning
confidence: 99%
“…Müller 1894;Bonaduce et al 1975;Montenegro et al 1996;Sciuto 2014;Frezza and Di Bella 2015) and Pleistocene (e.g. Ruggieri 1984;Ciampo 2003;Hastrup and Thomsen 2005a, b;Faranda and Gliozzi 2008;Aiello et al 2015) ostracod assemblages from Mediterranean subbasins is extensive, studies combining benthic Foraminifera and Ostracoda are scarce (Angue Minto'o et al 2015;Stalder et al 2015).…”
Section: Introductionmentioning
confidence: 99%